Relationship of cow weight, cow condition and dosage of prostaglandin on synchronized heat - D. Simms; L. Corah (Kansas Agricultural Experiment Station Research Reports, 1984)
Simmental cows on two Kansas ranches received either 2 or 3 ml injections of prostaglandin cloprostenol (Estrumate). Dose levels had little effect on response rate in either small or large cows. However, for each unit increase in body condition score, 12% more cows expressed heat.
Keywords: Cattlemen& #x27; s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Weight; Body condition score; Prostaglandin